(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Nutritional intervention is an effort to overcome nutritional problems with programs such as giving Fe and calcium tablets to pregnant women, giving zinc to children. To find out the factors that cause stunting and the effectiveness of Nutrition Interventions in Stunting Toddlers. This type of research is survey research with a cross-sectional design. The research sample was children aged 0-59 months with short or very short criteria, totaling 60 respondents. Sampling technique is purposive. Data analysis through Univariate and Multivariate. Univariate analysis to provide an overview of the prevalence of stunting in children aged 0-59 months and Multivariate Analysis to see the initial relationship of risk factors for stunting in children 0-59 months and the effectiveness of Nutrition Interventions for Stunting Toddlers. The analysis was performed by binary logistic regression. Of the risk factors for stunting found 5 factors that correlated with stunting, namely history of exclusive breastfeeding, p-value 0.007 <0.05 (OR 0.111, 95% CI 0.023 – 0.541), history of complementary feeding p-value 0.044 < 0, 05 (OR 0.297, 95% CI 0.091 – 0.970), the diversity of food content p-value 0.095 <0.10 and the odds ratio value of 2.743. Means that the diversity of food content consumed affects stunting by 2.743 times greater, nutritional adequacy p-value 0.042 <0.05 and odds ratio value of 3.429, meaning that nutritional adequacy affects stunting by 3,429 times greater and Immunity of toddlers with stunting p-value 0.029 <0.05 and OR 0.268, 95% CI 0.82 - 0.876. For the Nutrition Interventions studied in this study in the form of an intervention approach to pregnant women through supplementation of Fe tablets with a p-value of 0.02 <0.05 and an odds ratio of 0.194 and supplementary feeding obtained a p-value of 0.011 <0.05 and an odds ratio of 4.464. There is a significant relationship between the Nutritional Intervention of Fe tablet supplementation and feeding with stunting. History of complementary feeding, exclusive breastfeeding, nutritional adequacy, diversity of food content and immunity have an impact on stunting in toddlers. The main interventions that can be done to reduce stunting are by increasing good nutrition for pregnant and lactating women and conducting early intervention in cases of malnutrition by fulfilling a diet high in protein.